1995
DOI: 10.1074/jbc.270.31.18191
|View full text |Cite
|
Sign up to set email alerts
|

Thiophosphorylation of the 130-kDa Subunit Is Associated with a Decreased Activity of Myosin Light Chain Phosphatase in α-Toxin-permeabilized Smooth Muscle

Abstract: Pretreatment of alpha-toxin-permeabilized smooth muscle with ATP gamma S (adenosine 5'-O-(thiotriphosphate)) under conditions resulting in minimal (< 1%) thiophosphorylation of the myosin light chain increases the subsequent calcium sensitivity of force output and myosin light chain phosphorylation. The change in calcium sensitivity results at least in part from a 5-fold decrease in myosin light chain phosphatase activity. One of the few proteins thiophosphorylated under these conditions is the 130-kDa subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 28 publications
4
99
0
1
Order By: Relevance
“…Inhibition of MLCP by rho also was shown with cultured vascular SMCs (Noda et al, 1995). Phosphorylation of M130 was shown to inhibit phosphatase activity in skinned muscle (Trinkle-Mulcahy et al, 1995). The activity of MLCP also is regulated by phosphorylation of a threonine residue in M130 in vitro (Ichikawa et al, 1996b).…”
Section: Localization Of Mlcp In Migrating Fibroblastsmentioning
confidence: 96%
See 1 more Smart Citation
“…Inhibition of MLCP by rho also was shown with cultured vascular SMCs (Noda et al, 1995). Phosphorylation of M130 was shown to inhibit phosphatase activity in skinned muscle (Trinkle-Mulcahy et al, 1995). The activity of MLCP also is regulated by phosphorylation of a threonine residue in M130 in vitro (Ichikawa et al, 1996b).…”
Section: Localization Of Mlcp In Migrating Fibroblastsmentioning
confidence: 96%
“…Monoclonal antibody for M130 was made as described before (Trinkle-Mulcahy et al, 1995). Rabbit polyclonal antibody against M130 was made against a recombinant protein encoding 1-674 of M130 (Ichikawa et al, 1996b) and purified through DEAE Affi-gel blue (Bio-Rad, Hercules, CA).…”
Section: Antibody Reagents and Western Blotting Analysismentioning
confidence: 99%
“…Calcium-activated MLC kinase or Rho-associated kinase (' ROCK '), which are activated by the small GTPase Rho, phosphorylate MYPT1\2, which leads to the inhibition of PP1 activity toward MLC [17,[61][62][63]. The major protein phosphatase that dephosphorylates myosin has been described as a heterotrimer containing the PP1 catalytic subunit, an approx.…”
Section: Discussionmentioning
confidence: 99%
“…One such mechanism is via phosphorylation of MYPT1 at an inhibitory site, ie, T695 in the larger chicken gizzard isoform. 29 This originated with the observation of Trinkle-Mulcahy et al 31 that incubation of permeabilized rabbit portal vein strips with ATP␥S caused thiophosphorylation of MYPT1 and inhibition of MP activity. Subsequently, it was found that a kinase(s) that co-purified with the MP preparations also phosphorylated MYPT1 at T695 and inhibited phosphatase activity.…”
Section: Shin Et Al Myosin Phosphatase Subunit Localization 551mentioning
confidence: 99%